Plastic Analysis of Metal Surface Layers Undergoing the Roller Burnishing Process - Gambin, W. (Engineering Transactions, 1996)
The roller burnishing process as a particular case of the rolling contact problem is considered. The hardening of the burnished surface layers considerably improves the mechanical properties of machine elements. However, in some cases, softening of a thin contact layer underneath the rolled material occurs. It is caused by the overheating due to a high speed of the rolling or by the plastic strain cumulation due to a multiple rolling repetition. As an effect, peeling and cracking of the rolled surface layers appears. The softening effect is taken into account in the present analysis of the roller burnishing process. The proposed slip-line field and the corresponding velocity field are obtained by a modification of the simplified solution proposed by COLLINS [3]. The new solution describes the "seizing effect" observed on some micrographs of metal surface layers. The bounds for the vertical load, applied to the roller and causing this effect, are given as functions of material softening.